CLINICAL USE OF THREE-DIMENSIONAL ULTRASOUND (3D US) IN THE FIELD OF HEPATOBILIARY SYSTEM AND THE REST OF THE ABDOMEN - Mirjana Brvar; Eldar Gadžijev; Stanko Pšeničnik (Zdravniški Vestnik, 2003)
Background. We are presenting our first experiences with a new method of ultrasound checkup of abdominal organs. Conclusions. 3D US can serve as a useful supplement to the classical 2D examination since it can provide more information necessary for the diagnostic process. We believe that technological development will eliminate the majority of deficiencies of this method and thus increase its accuracy and applicability.